Establishing Criteria Levels For Some Anthropometric Measurement for Volleyball Primer League Female Players - Noor , Samah; Talip, Sara (Journal of Physical Education, 2019)
The importance of the research lies in developing criteria and levels for some physical variables for Iraqi volleyball Premier League. The problem of research lies in the lack of criteria and levels to determine anthropometric measurements and establishing degrees and criteria levels.  The researchers used the descriptive methods on (48) out of (72) and 66% of the original society. The most important results reached by the researcher was the development of degrees and standard levels for some anthropometric  measurements and that the standards that have been developed and describe the real level of the sample since most of the results extracted between the levels (weak and acceptable) and this indicates the lack of interest in the scientific means of choosing the players correctly based on recent studies.